Aprendizagem da docência universitária: a gestão em contextos emergentes - Dewes, Andiara (2019)
The times and spaces of Higher Education have been driven to new configurations, especially through public policies of expansion and democratization and the technological context consolidating an increasingly technological-digital daily life. At this juncture, the teaching work of university professors is amplified and complexified. Given this, in this study, we focus on the performance of professors as university managers. We define as a problem of the study: what are the repercussions of the professor's/manager's performance on professional development in emerging contexts? Our general objective was to understand the professional development of the teacher/manager in emerging contexts. The research field was a federal public university and we had as subjects professors who acted as managers in the institution in March 2018. As for the methodological design, it is a qualitative research socio-cultural narrative. As theoretical-methodological substrate we have, among others, studies by Vygotsky (1993, 1994, 2007), Bakhtin (1993, 1997, 2010, 2011), Freitas and Ramos (2010), Bolzan (2002 - 2016), Clandinin and Connelly ( 1995), Morosini (2014, 2016), Pachane (2015), Pimenta and Anastaciou (2010), Sousa (2011), Zabalza (2004). The construction of this research had two immersions in the investigative field: the first resulted in a mapping of who are the professors/managers of the researched university and in the second we had the proposal of a questionnaire to the teachers/managers, expanding and qualifying the survey of aspects of their profile from those already listed in the first immersion, as well as the identification of some of their conceptions through their narratives obtained with descriptive answers. Thus, we had as investigative instruments and procedures an exploratory study from the documentary analysis of information available on the institution's official website and, following, an exploratory questionnaire. The production of the findings was made from quantitative data, focusing on an explanatory-interpretative perspective, with the open questions asked in the questionnaire as elements capable of amplifying the understanding of the university management process. Thus, the major category produced is university teaching learning, having as dimensions the performance in higher education and the production of management knowledge. Through the discussion built we consolidate the constitution of university teaching by the dimensions of teaching (undergraduate and graduate), research, extension, and management. The learning of university teaching is understood as the process of becoming a university professor, considering these dimensions in which he can act and the respective demands, challenges and possibilities inherent to each one and which articulate, reflecting both the organization of teaching work and in professional development. Understanding that the learning that professors make when becoming managers implies the professional development of teachers, therefore the identification and understanding of this process brings the possibility of qualifying and enhancing both teacher learning and training actions that aim to offer some substrate to teachers as to acting as university managers. Given this, we identified that if there is no training/preparation for acting in management, there is the production of management knowledge having as a substrate the previous knowledge, which is triggered and lead the professors to produce new specific knowledge about university management.